2015
DOI: 10.1016/j.jmii.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma polymorphisms associated with susceptibility to tuberculosis in a Han Taiwanese population

Abstract: The IFN-γ polymorphisms, rs1861494, rs2069718, and rs2430561, may confer the risk of TB in Han Taiwanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 16 publications
4
9
1
2
Order By: Relevance
“…Statistical analysis showed that genotype TA causes a 1.76‐fold increase in susceptibility to TB (Table ). Our findings are in accordance with those of previous studies in Taiwanese populations and populations of southeastern Iran .…”
Section: Discussionsupporting
confidence: 93%
“…Statistical analysis showed that genotype TA causes a 1.76‐fold increase in susceptibility to TB (Table ). Our findings are in accordance with those of previous studies in Taiwanese populations and populations of southeastern Iran .…”
Section: Discussionsupporting
confidence: 93%
“… P h : value of Q -test for heterogeneity test; P : Z -test for the statistical significance of the OR. HWE: Except for seven studies[ 20 , 25 , 30 , 34 , 40 , 42 , 47 ], the distribution of genotypes in the controls in remaining 35 studies was in agreement with HWE, and it reports the meta-analysis results of studies showing no deviation from the HWE. …”
Section: Resultsmentioning
confidence: 93%
“…[12] Bunun dışında VDBP proteinin bronkoalveoler lavaj sıvısında bulunması nedeniyle kronik obstrüktif akciğer hastalığı (KOAH), tüberküloz gibi hastalıklarda işlevi olabileceği düşünülmektedir. [13] Akciğer patogenezinde yer alan en önemli etmenlerden biri de tütün kullanımıdır. Sigara dumanında bulunan birçok toksik ve karsinojenik bileşen DNA, protein ve lipidler ile etkileşime girerek normal fizyolojik işlevin bozulmasına ve sağlık sorunlarına neden olmaktadır.…”
Section: Bulgularunclassified
“…[7] Son yıllarda ayrıca VDBP'nin kardiyovasküler hastalıklar, otoimmün bozukluklar, diyabet, astım, Alzheimer ve tüberküloz gelişiminde ve çeşitli kanserlerde görevler aldığına dair kanıtların bulunduğu çalışmalar bulunmasına rağmen, eldeki veriler birbiriyle çelişir niteliktedir. [7][8][9][10] Bu nedenle çalışmamızda GC geninin farklı alellerinin akciğer kanser etyolojisindeki yerini araştırmayı hedefledik. …”
unclassified